Studi penambahan etilena glikol dalam menghambat pembentukan metana hidrat pada proses pemurnian gas alam - Muslikhin Hidayat; Danang Tri hartanto; Muhammad Mufti Aziz; Sutijan Aziz (Jurnal Rekayasa Proses, 2020)
The gas processing facilities are designed to significantly reduce the impurities such as water vapor, heavy hydrocarbon, carbon dioxide, carbonyl sulfide (COS), benzene-toluene-xylene (BTX), mercaptane, and the sulfur compounds. A small amount of those compounds in natural gas is not preferable since they disturb the next processes. It was proposed to decrease natural gas's operating temperature to -20 ⁰F to remove the impurities from natural gas. The decrease of the natural gas's operating temperature has some consequences to the gas mixers such as hydrate formation at high pressure and low temperature, solidification of ethylene glycol (EG) solution, and the icing of the surface due to low temperature on the surface of chiller (three constraints). The Aspen Hysys 8.8 was used to obtain the suitable flowrate and concentration of the EG solution injected into the natural gas. Peng-Robinson's model was considered the most appropriate thermodynamic property model, and thus it has been applied for this research. The calculation results showed that the EG solution injection would reduce the hydrate formation due to water vapor absorption in the natural gas by EG. The EG solution's flowrate and concentration were varied from 20,000-2,000,000 lb/hr and 80-90 wt.%. When the separation was carried out at the operating temperature of -20 ⁰F, the EG solution's concentration fulfilling the requirement was of 80-84 wt.% with the flowrate of EG solution of 900,000 lb/hr and even more. This amount is not operable. More focused investigation was done for the variation of the operating temperature. Increasing operating temperature significantly reduced the flowrate of EG solution to about 200,000 lb/hr. An alternative process was proposed by focusing on two concentration cases of 80 and 85 % of weight at the low flow rate of EG solution, respectively. These simulations were intended to predict impurities' concentration in the effluent of Dew Point Control Unit (DPCU). The concentrations of BTX, heavy hydrocarbon, mercaptane, and COS flowing out of DPCU were 428.1 ppm, 378.4 ppm, 104 ppm, and 13.3 ppm, respectively. The concentrations of BTX and heavy hydrocarbon are greater than the minimum standard required. It is needed to install an absorber to absorb BTX and heavy hydrocarbon. However, the absorber capacity will be much smaller than if the temperature of natural gas is not decreased and not injected by the EG solution.